Ecology, Metabolism, and Genetics of Ruminal Selenomonads - Ricke, S.C.; Martin, S.A.; Nisbet, D.J.
Selenomonas ruminantium is one of the more prominent and functionally diverse bacteria present in the rumen and can survive under a wide range of nutritional fluctuations. Selenomonas is not a degrader of complex polysaccharides associated with dietary plant cell wall components, but is important in the utilization of soluble carbohydrates released from initial hydrolysis of these polymers by other ruminal bacteria. Selenomonads have multiple carbon flow routes for carbohydrate catabolism and ATP generation, and subspecies differ in their ability to use lactate. Some soluble carbohydrates (glucose, sucrose)appear to be transported via the phosphoenolpyruvate phosphotransferase system, while arabinose and xylose are transported by proton symport. High cell yields and the presence of electron transport components in Selenomonas strains has been documented repeatedly and this may partially account for the energy partitioning observed between energy consumed for growth and maintenance functions. Most strains can utilize ammonia, protein, and/or amino acids as a nitrogen source. Some strains can hydrolyze urea and/or reduce nitrate and use the ammonia for the biosynthesis of amino acids. Experimental evidence suggests that ammonia assimilatory enzymes in some strains may possess unique properties with respect to other presumably similar bacteria. Little is known about the genetics of ruminal selenomonads. Plasmid DNA has been isolated from some strains, but it is unknown what physiological functions may be encoded on these extrachromosomal elements. Due to the predominance of S. ruminantium in the rumen, it is an ideal candidate for genetic manipulation. Once the genetics of this bacterium are better understood, it may be possible to amplify its role in the rumen.
Keywords: SELENOMONAS RUMINANTIUM; RUMEN; ECOLOGY; METABOLISM; GENETICS